2020
DOI: 10.1001/jamainternmed.2020.1835
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hospitalization With Hemorrhage Among Older Adults Taking Clarithromycin vs Azithromycin and Direct Oral Anticoagulants

Abstract: nticoagulant-associated hemorrhage is one of the most common adverse drug reactions requiring hospitalization among individuals of advanced age, with a 2-fold increase among those older than 75 years. 1 Identification and avoidance of dangerous drug-drug interactions are associated with a significant reduction in adverse events and improvement in evidence-based prescription patterns.During the last decade, direct oral anticoagulants (DO-ACs) have supplanted traditional vitamin K antagonists as the anticoagulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 59 publications
0
40
1
1
Order By: Relevance
“…For example, a recent large database analysis showed that the concurrent use of clarithromycin (increases DOAC levels) and DOACs led to an increase in clinically relevant bleeding events (adjusted hazard ratio [HR] 1.71, 95% confidence interval [CI] 1.20-2.45 for hemorrhage requiring hospitalization) compared to azithromycin (minimal effects on DOAC metabolism). 17 However, data regarding concurrent use of DOACs and targeted anticancer therapies are limited. In addition, some targeted anticancer therapies such as ibrutinib can increase the risk of bleeding in the absence of anticoagulants by other mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent large database analysis showed that the concurrent use of clarithromycin (increases DOAC levels) and DOACs led to an increase in clinically relevant bleeding events (adjusted hazard ratio [HR] 1.71, 95% confidence interval [CI] 1.20-2.45 for hemorrhage requiring hospitalization) compared to azithromycin (minimal effects on DOAC metabolism). 17 However, data regarding concurrent use of DOACs and targeted anticancer therapies are limited. In addition, some targeted anticancer therapies such as ibrutinib can increase the risk of bleeding in the absence of anticoagulants by other mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Limited pharmacokinetic studies have shown that concurrent use of medications involving both P‐gp and CYP3A4 metabolism could influence DOAC drug levels in vitro , but whether these findings translate into clinically relevant events has not been established. For example, a recent large database analysis showed that the concurrent use of clarithromycin (increases DOAC levels) and DOACs led to an increase in clinically relevant bleeding events (adjusted hazard ratio [HR] 1.71, 95% confidence interval [CI] 1.20–2.45 for hemorrhage requiring hospitalization) compared to azithromycin (minimal effects on DOAC metabolism) 17 . However, data regarding concurrent use of DOACs and targeted anticancer therapies are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Another study that examined concomitant use of DOACs with clarithromycin or azithromycin revealed that the use of clarithromycin, which is a potent inhibitor of CYP3A4 and P-gp, led to an increased rate of hemorrhage requiring hospitalization compared with azithromycin, a mild inhibitor of CYP3A4 and P-gp. 66,67 Antineoplastic agents that might influence the efficacy and safety of DOACs are paclitaxel, bicalutamide, enzalutamide, certain tyrosine kinase inhibitors, and abiraterone, and supportive care medications include dexamethasone, prednisone, azole antifungals, and neurokinin-1 antagonists. 68 While a recent posthoc analysis on participants in the CARAVAGGIO study showed comparative efficacy and safety of apixaban in patients treated or not treated with anticancer agents.…”
Section: Recurrent Venous Thromboembolism During Anticoagulationmentioning
confidence: 99%
“…In the general population, data addressing DDIs between DOACs and other medications are limited, but a few recent studies have provided some insights. A large database analysis showed that concomitant prescription of clarithromycin (a potent inhibitor of P‐gp and CYP3A4) and DOACs caused a 1.71‐fold increased risk of hospitalization for major hemorrhage within 30 days of concurrent use, compared with concomitant prescription of azithromycin (minimal effect on P‐gp and CYP3A4) or without concurrent use [18]. Another single‐center retrospective study showed that use of combined P‐gp and moderate CYP3A4 inhibitors (such as amiodarone, diltiazem, etc.)…”
Section: Concomitant Use Of Strong Inhibitors or Inducers Of Both Cytmentioning
confidence: 99%